PEGARUH HARGA DAN KUALITAS PRODUK TERHADAP KEPUTUSAN PETANI MEMBELI BIBIT SAWIT DI PT. BIO NUSANTARA TEKNOLOGI BENGKULU - Nurzam Nurzam; Rani Sari Fauziah; Karona Cahya Susena (UNIVED Press, 2020)
Nurzam, Rani Sari Fauziah, dan Karona Cahya Susena; This research aims to determine the influence of price and quality of seedlings against farmers ' decision to buy palm seed in PT. Bio Nusantara Teknologi Bengkulu. This type of research is descriptive with a quantiative approach. The type of data used is primary data obtained through the dissemination of questionnaires and observations. Respondents in the research were farmers who bought oil palm seedlings at PT. Bio Nusantara Teknologi Bengkulu amounting to 50 people. Sample of the research is taken with acidental sampling technique. Data analysis methods used multiple regression analyses. From the results of the research acquired that: (1) The price has a positive effect and significant to the decision of farmers to buy oil palm seedlings in PT. Bio Nusantara Teknologi Bengkulu. This result means that if the seedling Affordable, then farmers ' decision to buy seedlings will be increasingly tingi; (2) The seed quality is positive and significant to the decision of farmers buying oil palm seedlings in PT. Bio Nusantara Teknologi Bengkulu. This result means that if the seed quality is being perceived to be more high, then the decision of farmers to buy seedlings will be more high; and (3) prices and quality of seedlings influence POSITF and significant to the decision of farmers buy oil palm seedlings in PT. Bio Nusantara Teknologi Bengkulu. This result means that if the seeds are perceived to be affordable and seed quality is getting better, then the decision of farmers buying seeds will be higher. Keywords: price, product quality, decision